A Self‐Powered, Sub‐nanosecond‐Response Solution‐Processed Hybrid Perovskite Photodetector for Time‐Resolved Photoluminescence‐Lifetime Detection. Issue 48 (26th October 2016) - Shen, Liang; Fang, Yanjun; Wang, Dong; Bai, Yang; Deng, Yehao; Wang, Mengmeng; Lu, Yongfeng; Huang, Jinsong
Abstract : A self‐powered, solution‐processed perovskite photodetector with sub‐nanosecond response time is presented. Eliminating charge trapping and removing the constraints from the resistance–capacitance constant increases the response speed, which enables them to be applied in a homemade, time‐resolved photoluminescence system that successfully resolves the decay process of typical fluorescence and phosphorescent materials with a recombination lifetime from several nanoseconds to microseconds.